Management and Outcomes of Unilateral Group D Tumors in Retinoblastoma - Amin, Saima (Clin Ophthalmol, 2021)
PURPOSE: Retinoblastoma presents most commonly as advanced unilateral disease, particularly in developing countries for which primary enucleation has been the preferred method of treatment. However, with the evolution of newer treatment modalities including intravitreal chemotherapy, intra-arterial chemotherapy and newer chemotherapeutic combinations, a trend towards more conservative approaches is being observed. Our aim is to evaluate outcomes of group D eyes following conservative and non-conservative treatment options. PATIENTS AND METHODS: The ocular oncology database was used to identify eyes with unilateral retinoblastoma that fulfilled the International Intraocular Retinoblastoma Classification (IIRC) group D criteria from August 2010 to August 2018 and these were retrospectively reviewed. Overall, 39 eyes were identified. RESULTS: Nineteen (49%) eyes underwent primary enucleation and 20 (51%) received eye-conserving treatment. Eye salvage was possible in 15 (75%) eyes in the attempted salvage group. None of the patient revealed signs of metastasis. All eyes received conventional chemotherapy (carboplatin, vincristine, etoposide) and focal laser therapy. Additional treatment modalities offered included intravitreal chemotherapy, intra-arterial chemotherapy and topotecan. Three (11%) eyes in the primary enucleation group showed high-risk features on histopathology and none developed metastasis. CONCLUSION: The results of the study seem promising and conservative measures can be adopted in selected unilateral group D eyes.